Presidential Expressions and Viewer Emotion: Counterempathic Responses to Televised Leader Displays - Bucy, Erik P.; Bradley, Samuel D. (Social Science Information, 2004)
Despite the biological predisposition to recognize and mimic facial expressions, research has shown that contextual or experiential factors may elicit emotionally incongruent, or counterempathic, responses. This experimental study reports how counterempathic responses to televised leader displays may be evoked in political communication. Findings suggest that unexpected nonverbal communication is subject to cognitive appraisal, which may influence emotional responding. Subjects were shown a series of four news stories, each followed by a 30-second televised reaction of President Bill Clinton. The story–reaction sequences varied by story topic, level of emotion and degree of leader display appropriateness. Physiological (heart rate, skin conductance and facial muscle activation, or EMG) and emotional self-report measures indicated that evaluations of display appropriateness moderated how much attention was given to the display, the affective direction of viewers’ facial muscle activation and the level of autonomic activation, or arousal. The EMG data showed that viewers frowned in response to positive expressive displays that followed positive news. Smiling activation also decreased for high-intensity, positive displays. By manipulating the valence and intensity of the associated news event, facial mimicry, and emotional responses to leaders generally, are shown to be situationally influenced by the larger social and informational context.